Peran dan Kendala yang dihadapi Jaksa dalam Melakukan Pengawasan Terhadap Pelaksanaan Putusan Pidana Bersyarat - Ramadhoni, Arief; Suratman, Teguh; Anggriawan, Ferry (Postgraduate University of Merdeka Malang, 2023)
One form of alternative punishment that is quite often used in developing criminal offenders is conditional punishment. Conditional sentences are decided by a court judge with conditions, namely that their implementation is supervised by an authorized officer, intended to improve the convict so that he is not influenced by prison subculture, conditional sentences are also intended to prevent the occurrence of crime. Based on the background of the problem above, this article aims to examine and analyze the role of prosecutors in supervising the implementation of criminal decisions and the obstacles faced by prosecutors in supervising the implementation of conditional criminal decisions at the Sampang District Prosecutor's Office. This research uses legal science research with empirical aspects or non-doctrinal legal research or socio-legal research with a descriptive qualitative research approach. The results of this research are the implementation of supervision of conditional criminal decisions carried out by prosecutors at the Sampang District Prosecutor's Office only by requiring convicts to report within a certain period of time (during the probation period), in addition to coordinating with the police, BAPAS and with the heads of the villages where they are located. the conditional convict's domicile for monitoring by sending a copy of the conditional sentence notification report letter (P-51). The obstacles faced by prosecutors at the Sampang District Prosecutor's Office in implementing supervision of conditional criminal decisions are; legal factors, law enforcement factors, facility factors and community legal culture factors.